2019
DOI: 10.1111/bju.14872
|View full text |Cite
|
Sign up to set email alerts
|

The natural history of untreated muscle‐invasive bladder cancer

Abstract: ConclusionsUntreated patients with MIBC are at very high risk of nearterm CSM. These findings may help balance the risks vs benefits of integrating curative intent therapy particularly in older patients with MIBC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(47 citation statements)
references
References 26 publications
1
46
0
Order By: Relevance
“…Although perioperative complication rates range around 50% in our entire study cohort, we found acceptable perioperative complication rates, ranging well among the reported 24–61% [23-25]. However, if no treatment is offered to this group of patients, they are at high risk of developing metastatic disease and will most likely die due to the disease itself, as shown in the study of Martini et al [27]. Without any treatment, the risk of dying from MIBC as well as any other cause increases (HR 2.02 and 2.63, respectively) [27].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Although perioperative complication rates range around 50% in our entire study cohort, we found acceptable perioperative complication rates, ranging well among the reported 24–61% [23-25]. However, if no treatment is offered to this group of patients, they are at high risk of developing metastatic disease and will most likely die due to the disease itself, as shown in the study of Martini et al [27]. Without any treatment, the risk of dying from MIBC as well as any other cause increases (HR 2.02 and 2.63, respectively) [27].…”
Section: Discussionsupporting
confidence: 82%
“…However, if no treatment is offered to this group of patients, they are at high risk of developing metastatic disease and will most likely die due to the disease itself, as shown in the study of Martini et al [27]. Without any treatment, the risk of dying from MIBC as well as any other cause increases (HR 2.02 and 2.63, respectively) [27]. While survival of the oldest-old is clearly limited, there is a significant benefit compared to a 2-year-survival rate of 14%, if left untreated [28].…”
Section: Discussionmentioning
confidence: 99%
“…Although, we cannot compare patients treated with chemotherapy with those not treated with chemotherapy since the tumor biology and prognosis are quite different, we saw no positive effect of the application of chemotherapy in the N0 patients, at least in our patient cohort. Recently, a study of muscle invasive BCa in Sweden showed that patients treated with radio/chemotherapy or radiotherapy had a better OS and DSS than untreated patients [47]. However, treated patients were not further stratified by their lymph node status.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically in elderly patients, concerns have been expressed about the higher morbidity and mortality rates associated with RC [4], resulting in <20% of octogenarians with MIBC undergoing RC, which indicates that a significant number of patients are not currently being offered definitive treatment [5]. The evidence indicates that 85% of untreated patients with localized MIBC succumb to the disease within 5 years of the diagnosis, whereas <10% die from other causes [6]. At the same time, reported high-grade complication rates in elderly populations for open RC (ORC) have been up to 33%, and the 90-day mortality rates are approximately 15% [7][8][9].…”
Section: Introductionmentioning
confidence: 99%